Pengaruh Gaya Kepemimpinan Transformasional, Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan (Studi Pada PT. Central Cipta Abadi) - Rizqi Waladun Khoiri; Wawan Prahiawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this research is to find out how the employees of PT. Central Cipta Abadi in Cilegon City in relation to the work environment, motivation and transformational leadership style. Quantitative research methodology was applied. This research used 93 respondents as samples and populations. A technique known as non-probability sampling (saturated sample), to collect data based on questionnaires with measurements using an interval scale. SmartPLS 3.0 analysis tool, which consists of exterior and inner model tests as well as instrument tests. Based on data calculations carried out with SmartPLS 3.0, the following conclusions can be drawn: (1) The work environment has a positive and significant effect on employee performance; (2) There is no significant effect of transformative leadership style on employee performance; (3) Employee performance is positively influenced by work motivation and is significant in this case.